Perbandingan Hasil Belajar Menggunakan Model Reciprocal Learning Dan CIRC Dengan Memperhatikan Motivasi - Ana Annisa Fitri; Nurdin Nurdin; Tedi Rusman (FKIP Unila, 2019)
The learning method used by the teacher will influence the way students learn which one student with another student has a different way of learning. Currently educators are constantly trying to compile and apply various varied learning models so that students are interested and enthusiastic during economic learning, one of which is Reciprocal Learning and Cooperative Integrated Reading and Composition (CIRC). The research method used in this study is comparative research with an experimental approach. The experimental research design used in this study was a factorial design. Based on the results of data analysis and hypothesis testing, it was concluded that there were significant differences in the average economic learning outcomes of students learning using the Reciprocal Learning learning model compared to those using the Cooperative Integrated Reading and Composition (CIRC) learning model. The average economic learning outcomes for students taught using Reciprocal Learning learning models are higher than those taught with Cooperative Integrated Reading and Composition (CIRC) learning in students who have high learning motivation. Metode pembelajaran yang digunakan oleh guru akan berpengaruh terhadap cara belajar siswa yang mana antara siswa yang satu dengan siswa yang lainnya mempunyai cara belajar yang berbeda. Saat ini para pendidik terus-menerus berusaha menyusun dan menerapkan berbagai model pembelajaran yang variatif agar siswa tertarik dan bersemangat pada saat pembelajaran ekonomi, salahsatunyaadalahReciprocal Learning danCooperative Integrated Reading and Composition (CIRC).Metodepenelitianyangdigunakan dalam penelitian ini adalah penelitian komparatifdengan pendekatan eksperimen. Desain penelitian eksperimenyangdigunakan dalam penelitian ini adalah desain faktorial.Berdasarkan hasil analisis data dan pengujian hipotesis, diperoleh kesimpulan bahwa adaperbedaansignifikanrata-ratahasilbelajarekonomisiswayang pembelajarannyamenggunakanmodelpembelajaranReciprocal Learning dibandingkandenganyangmenggunakanmodelpembelajaranCooperative Integrated Reading and Composition (CIRC).Rata-ratahasilbelajarekonomipadasiswayangdiajarmenggunakanmodel pembelajaranReciprocal Learning lebihtinggidibandingkanyangdiajardenganpembelajaranCooperative Integrated Reading and Composition (CIRC)padasiswayangmemilikimotivasibelajartinggi Kata Kunci: Cooperative Integrated Reading and Composition (CIRC), motivasibelajar, Modelpembelajaran, Reciprocal Learning,